KAMPUNG ORGANIK SEBAGAI MODEL PENDIDIKAN LINGKUNGAN BERBASIS MASYARAKAT BAGI ANAK USIA DINI DI KOTA SEMARANG - Sukirman, Sukirman; Kusumandari, Rafika Bayu (UNIVERSITAS PGRI MADIUN, 2018)
Abstract. Organic village is the designation for the urban / rural are developing environmental management where whole communities to manage the environment by planting organic crops. Even they develop dengue mosquito eradication in a way that is natural to plant crops that are not favored by mosquitoes. Referring to the objectives to be achieved, the research program was designed with a